Effects of blended learning on reading comprehension and critical thinking skills of undergraduate ESL students - Bolandifar, Saeideh (2017)
Blended learning, as a combination of face-to-face instruction and computermediated instruction, has achieved an unprecedented popularity in higher education today. This is due to the fact that blended learning attempts to take advantage of the strengths of both learning environments. The present study therefore aimed to investigate the effects of blended learning instruction on Malaysian undergraduate ESL students’ reading comprehension and critical thinking skills. The study adopted a quasi-experimental design featuring a nonrandomized control group, pretest–posttest design which included a mid-test as well. A total of 42 undergraduate ESL students were assigned to two groups, namely the blended learning (experimental) group and the traditional face-to-face learning (control) group. The blended learning method of instruction using the course management system, Moodle was conducted as the research treatment for the blended learning group while the face-to-face instruction was conducted for the traditional face-toface learning group. Both quantitative and qualitative methods were applied to collect and analyze data. The TOEFL reading comprehension test, the Cornell Critical Thinking Test (CCTT, Level X), and the blended learning perception questionnaire were utilized to assess students’ reading comprehension, critical thinking skills, and the perception of blended learning implementation respectively. A content analysis method utilizing Newman, Webb, and Cochrane’s (1995) critical thinking model was employed to analyze the students’ discussion transcripts. In addition, semi-structured interviews were also conducted. The Repeated Measures ANOVA, Analysis of Covariance (ANCOVA), Independent Sample t-test, and chi-square test were used to analyze the data. The findings of the study revealed that both the blended learning group and the traditional face-to-face learning group improved greatly in their reading comprehension and critical thinking skills across the three testing periods of pre-tests, mid-tests, and post-tests. However, a statistically significant difference was found in reading comprehension and critical thinking skills between the blended learning and the traditional face-to-face learning groups. Findings from the blended learning perception questionnaire revealed highly positive attitudes toward the implementation of blended learning. The content analysis of the discussion transcripts indicated that the depth of critical thinking ratios of the blended learning group and the traditional face-to-face learning group improved significantly in which there was a significant difference between the depths of critical thinking ratios of the two groups. Qualitatively, the results showed that the students found blended learning as a new, effective, useful, and interesting method of instruction in improving their reading comprehension and critical thinking skills. These findings demonstrated that the proposed blended learning method of instruction was more effective in improving reading comprehension and critical thinking skills of undergraduate ESL students than the traditional face-to-face instruction. This method of instruction offers an alternative teaching and learning approach with an effective use of Moodle-supported strategy instruction which supports the constructivist theory of learning in order to enhance the reading comprehension and critical thinking skills of students.